Heterogeneity in the Persistence of Health: Evidence from a Monthly Micro Panel - Stephen Hoskins; David W. Johnston; Johannes S. Kunz; Michael A. Shields; Kevin E. Staub (Institute of Labor Economics (IZA), 2024)
Despite being widely used in health economics, dynamic models of health and healthcare typically assume that the persistence in these outcomes is the same for every individual. Understanding the extent and drivers of heterogeneity in persistence is essential for the design and evaluation of health interventions because persistence determines the dynamics and overall long-run effects of such interventions. This paper explores individual-level heterogeneity in the persistence of health outcomes. Using simple regression methods that do not place any restriction on the distribution of the heterogeneity in persistence, the paper documents substantial heterogeneity in health, medical expenditures, and healthcare use. We show that neglecting this heterogeneity leads to estimates that overstate the average persistence and can bias the coefficients of covariates. We find that between 75% and 87% of individuals display persistence and that this persistence is related to the individuals' personality and socio-economic characteristics.
Keywords: I10; I12; C23; 330; self-reported health; healthcare utilisation; dynamic panel data; state dependence; heterogeneity